Changes in body size and physical characteristics of South African under-20 rugby union players over a 13-year period - Lombard, W. P.; Durandt, J. J.; Masimla, H.; Green, M.; Lambert, M. I. (The Journal of Strength and Conditioning Research, 2015)
This study compared changes in the body size and physical characteristics of South African under-20 rugby union players over a 13-year period. A total of 453 South African under-20 players (forwards: n = 256 and backs: n = 197) underwent measurements of body mass, stature, muscular strength, endurance, and 10- and 40-m sprint times. A 2-way analysis of variance was used to determine significant differences for the main effects of position (forwards vs. backs) and time (1998-2010). The pooled data showed that forwards were significantly heavier (22%), taller (5%), and stronger (18%) than the backs. However, when 1 repetition maximum strength scores were adjusted for body mass, backs were stronger per kg body mass. Stature did not change over the 13-year period for both groups. There were, however, significant increases in muscular strength (50%), body mass (20%), and muscular endurance (50%). Furthermore, an improvement in sprint times over 40 (4%) and 10 m (7%) was evident over the period of the study. In conclusion, the players became heavier, stronger, taller, and improved their upper-body muscular endurance over the 13 years of the study. Furthermore, sprint times over 10 and 40 m improved over the same time period despite the increase in body mass. It can be speculated that the changes in physical characteristics of the players over time are possibly a consequence of (a) adaptations to the changing demands of the game and (b) advancements in training methods.